Egyptian tale from India: application of whole‐exome sequencing in diagnosis of atypical familial Mediterranean fever. (17th February 2017) - Sandhya, Pulukool; Vellarikkal, Shamsudheen Karuthedath; Nair, Aswin; Ravi, Rowmika; Mathew, John; Jayarajan, Rijith; Kumar, Anoop; Verma, Ankit; Sivadas, Ambily; Danda, Debashish; Sivasubbu, Sridhar; Scaria, Vinod
Abstract: Clinical diagnosis of autoinflammatory diseases requires a high degree of clinical suspicion and clinching molecular evidence to substantiate the diagnosis. This is more so in populations with low prevalence of these disorders. In this report, we describe the case of a young man from India with recurrent fever and persistent arthritis. The patient's forefathers were of Egyptian ancestry who practiced consanguinity. Molecular genetic analysis using whole‐exome sequencing suggested the presence of variants c.443A>T:p.E148V and c.442G>C:p.E148Q in the MEFV gene, earlier independently shown to be associated with familial Mediterranean fever (FMF) in a compound heterozygous state. The variants were further confirmed by capillary sequencing. This report also highlights the application of whole exome sequencing to delineate the allelic differences in the variants apart from serving as a quick genetic screening approach for autoinflammatory diseases. To the best of our knowledge, this is the first report of a compound heterozygosity for the two well‐characterized variants associated with atypical FMF in a patient.